PENGARUH REINFORCEMENT TERHADAP KEDISIPLINAN BELAJAR SISWA DI SMP NEGERI 05 BALIKPAPAN KALIMANTAN TIMUR - ACHMAD RUSLAN AFENDI; MUHAMMAD MAQSUDI (STIT DARUL ULUM KOTABARU, 2022)
This paper argues about the relationship between reinforcement and learning discipline of State Junior High School (SMPN) 5 Balikpapan students. As for the background in this research is the importance of reinforcement in the sense of positive or negative reinforcement in the process of creating student learning discipline. The problems discussed in this thesis can be formulated in the form of questions, namely how is reinforcement at SMP Negeri 5 Balikpapan, how is student learning discipline at SMP Negeri 5 Balikpapan, and is there a relationship between reinforcement. Based on the results of the research analyzed, it shows that the reinforcement given by the teachers of SMP Negeri 5 Balikpapan is in the very high category with a frequency of 55. 56%. The remaining 5. 56% are in the high category, 5. 56% are in the medium category, 1. 85% are in the low category. Meanwhile, the level of learning discipline of SMP 5 Balikpapan students is in the high category with a frequency of 7. 41. The remaining 5.56% is in the very high category, 3.70% is in the medium category and 3.70% is in the low category. Because the frequency results obtained at all levels are almost the same, it can be concluded that the learning discipline of SMP 05 Balikpapan students is in the high category. The results of the hypothesis test show that there is no relationship between reinforcement and student discipline at SMP Negeri 5 Balikpapan with a product moment correlation coefficient (r) of 0.606 in the interpretation table of correlation data, which is at a level between 0. 600-0. 800 the correlation is in the high category. The table value of the correlation coefficient for 5% is 0.666 and at a significance level of 1% is 0. 789. With the r count > r table. Thus, it is concluded that there is no correlation between reinforcement and student discipline at SMP Negeri 05 Balikpapan.